Food security indicators, measurement, and the impact of trade openness - Guha-Khasnobis, Basudeb; Acharya, Shabd S.; Davis, Benjamin 1964- (UNU-WIDER studies in development economics, 2007)
The fight against world hunger has recently been overshadowed by the drive to end poverty. Yet the growing importance of the WTO and its role in shaping the agricultural trade agenda, has serious implications for food security across the globe. This volume attempts to redress the balance and provide a much needed debate on this topic